Effects of Poverty, Income Inequality and Economic Growth to Environmental Quality Index (EQI) in 33 Province in Indonesia 2014-2019 - Anisa Bella Pertiwi; Aulia Hapsari Juwita; Suryanto Suryanto (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2021)
Shifting from the agriculture sector to the service sector has made Indonesia's economy rapidly grow and therefore a degradation in environmental quality. The degradation of the Environmental Quality Index (EQI) in 2019 is mostly caused by an increasing water pollution level. Income inequality and poverty in Indonesia is a problem that also causing the EQI degradation. There are 2 purposes of this article which are (1) to find out the effect of income inequality, poverty, and economic growth toward EQI (2) to find if there is causality between economic growth and EQI. The approach used in this article is a quantitative approach with a type of data is secondary data. This article used panel regression with Random Effect Model (REM) by combining cross-section data from 33 provinces in Indonesia and time-series data from 2014 – 2019. The causality between economic growth and EQI is calculated by using Granger Causality. The result shows that (1) economic growth and income inequality have a negative significant relationship toward EQI, but poverty hasn’t affect to EQI (2) There is no causality between economic growth and EQI because EQI can not affect economic growth.